Taller Vertical de Comunicaciones 02 (2009)
Selección de trabajos de los niveles 1 a 3 del taller.
Keywords: GARCÍA-PAGANI; ARQUITECTURA; ENSEÑANZA; TALLERES; FAU; UNLP; LA PLATA; BUENOS AIRES (PROV); ARGENTINA